Adipofascial Flap in the Recipient Incision Site for Coverage of Vascular Pedicle in Free Tissue Transfer. Issue 3 (March 2016) - Durand, Paul D.; Couto, Rafael A.; Isakov, Raymond; Gurunluoglu, Raffi; Bernard, Steven
Abstract : Summary: The recipient incision adipofascial flap offers a simple approach to address a tight skin closure over a vascular pedicle. This technique is not just fast and easy to perform but also adds little to no morbidity, removing a potential source of flap failure. Abstract : Supplemental Digital Content is available in the text.